Accumulation of colicin M protein and its biological activity in transgenic lettuce and mizuna plants - Shcherbak, Nataliia; Prochaska, Heike; Lystvan, Kateryna; Prokhorova, Yelizaveta; Giritch, Anatoli; Kuchuk, Mykola (Frontiers in Plant Science, 2023)
Food-borne illnesses caused by pathogenic Escherichia coli strains, especially enterohaemorrhagic E. coli (EHEC), are a serious public health problem, as debilitating disease and even death from such food poisonings have been repeatedly reported. Colicin M (ColM), a non-antibiotic antimicrobial protein produced by some strains of E. coli, has shown promising activity in controlling multiple enteropathogenic strains of E. coli and related pathogens. As contaminated green leafy vegetables are a frequent source of pathogenic E. coli infections, we genetically modified (GM) two edible crops, lettuce (Lactuca sativa L.) and mizuna (Brassica rapa subsp. nipposinica var. laciniata), to stably express the ColM gene and assessed the antibacterial activity of tissue extracts from these plants against selected E. coli strains in vitro. Transgenic plants of these species were developed using Agrobacterium-mediated transformation with a vector containing the ColM-coding gene (cma) under the control of the 35S promoter. Western blot analysis of recombinant ColM protein was performed in selected transgenic plants to confirm cma gene expression and quantify ColM accumulation. Plant tissue extractsExtracts of transgenic plants expressing ColM showed significant activity against two major strains of EHEC (O157:H7 and O104:H4) as well as E. coli strains resistant to beta-lactam- and carbapenem-class antibiotics. Importantly, the antibacterial activity persisted in several subsequent generations of transgenic lettuce and mizuna plants that stably expressed the ColM gene. Further, the activity remained stable without decrease in dried (up to 40°C) plant material for at least 3 months. In addition, our results also show that the antibacterial activity of dried (up to 40°C) biomass of transgenic plants remained stable without a decrease for at least three months.